The role of informational content of visual speech in an audiovisual cocktail party: Evidence from cortical oscillations in young and old participants. (4th September 2022) - Begau, Alexandra; Klatt, Laura‐Isabelle; Schneider, Daniel; Wascher, Edmund; Getzmann, Stephan
Abstract: Age‐related differences in the processing of audiovisual speech in a multi‐talker environment were investigated analysing event‐related spectral perturbations (ERSPs), focusing on theta, alpha and beta oscillations that are assumed to reflect conflict processing, multisensory integration and attentional mechanisms, respectively. Eighteen older and 21 younger healthy adults completed a two‐alternative forced‐choice word discrimination task, responding to audiovisual speech stimuli. In a cocktail‐party scenario with two competing talkers (located at −15° and 15° azimuth), target words (/yes/or/no/) appeared at a pre‐defined (attended) position, distractor words at the other position. In two audiovisual conditions, acoustic speech was combined either with informative or uninformative visual speech. While a behavioural benefit for informative visual speech occurred for both age groups, differences between audiovisual conditions in the theta and beta band were only present for older adults. A stronger increase in theta perturbations for stimuli containing uninformative visual speech could be associated with early conflict processing, while a stronger suppression in beta perturbations for informative visual speech could be associated to audiovisual integration. Compared to the younger group, the older group showed generally stronger beta perturbations. No condition differences in the alpha band were found. Overall, the findings suggest age‐related differences in audiovisual speech integration in a multi‐talker environment. While the behavioural benefit of informative visual speech was unaffected by age, older adults had a stronger need for cognitive control when processing conflicting audiovisual speech input. Furthermore, mechanisms of audiovisual integration are differently activated depending on the informational content of the visual information. Abstract : While a behavioural benefit for informative visual speech occurred for both groups, only older adults showed audiovisual condition differences in the theta and beta band. A stronger increase in theta perturbations for uninformative visual speech stimuli may be linked to early conflict processing. Stronger beta suppression for informative visual speech could be linked to audiovisual integration. Compared to the younger group, the older group showed generally stronger beta perturbations.